Educational technology innovation during the COVID-19 pandemic - Alfath Rizq Denadi; Wafa Nabilah Sopyan (Curricula: Journal of Curriculum Development, 2022)
Innovations in education are continuously being made to continue learning when COVID-19 pandemic. One of solution for dealing with negative impact of pandemic in the domain of education is to innovate accompanied by technology or to innovate in the elements of learning to achieve educational and the learning goals. The purpose for this research is proposed as an overview of educational innovations in Indonesia during COVID-19 pandemic. This research use a descriptive research method and descriptive content analysis study. Research analysis is carried out on international articles, national articles, and other sources regarding learning solutions for the pandemic by making innovations in the field of educational technology. The use of technology in learning cannot be separated in distance learning for COVID-19 pandemic. Therefore, to solve the problem of education for this pandemic, innovations are made not only in the technology used in learning, but there needs to be innovation in the elements of learning to achieve educational goals during this pandemic.